Fluid Flow Analysis of Stern Hull MV. Kelola Mina Makmur 150 GT Based Engine Propeller and Hull Matching Using Actuator Disk Propeller Method - Irfan Syarif Arief; Tony Bambang Musriyadi; Anwar Sahid (International Journal of Marine Engineering Innovation and Research, 2021)
The results of the simulation used a propeller disk actuator method that models the propeller effect without modeling a real propeller. Direct optimization will be calculated using the CFD method of each variation of the clearance propeller configuration indicating that the amount of propulsion efficiency produced is very dependent on the clearance propeller. The most optimal propulsion efficiency occurs at a distance of 0.738 m from the steering shaft with a Dprop = 0.88, KT = 0.22, KQ = 0.028, and J = 0.40 besides having an advance velocity visualized with a Va = 10.6 knots which has a 50% propulsion efficiency, which the value will decrease according to the reduction in distance propeller. The less efficiency of the propulsion produced in the clearance propeller between -0.162 - 0.438 m from the steering shaft. This is because the slope angle between the entry of water and the longitudinal axis of the ship's hull on the stern exceeds the required conditions.